Position in Corporate Network, Performance and Strategic Risks - Justyna Światowiec-Szczepańska; Michał Zdziarski (Problemy Zarządzania, 2016)
The fundamental question of management research is to explore the determinants of differences in company performance. These determinants are both exogenous and endogenous. Network literature highlights the importance of access to external resources available to a firm through its network. The main objective of the presented research is primarily to test the relationship between the performance of companies and their position within a network. The empirical field of this research covered companies listed on the Warsaw Stock Exchange. We test effects of structural positions in two networks among the same set of companies linked by boards and ownership ties. Social network analysis (SNA) methods were used to determine positional characteristics of firms. The results of our research underline the importance of ownership links and firms’ positions in corporate networks for firms’ performance and strategic risk.